Public Capital in the Private Sector of Italian Economy - Salvatore Amico Roxas; Antonio Cristofaro; Giuseppe Piroli (Economics and Econometrics Research Institute (EERI), 2012)
This paper investigates how the services of public capital affect the different sectors of private economy in Italy. For this purpose, we use a trans-logarithmic cost function which includes infrastructure's services as a quasi-fixed free input. This approach allows to measure the effects of public capital in terms of cost reduction, productivity and distortion in the use of private inputs of production. We find that that the effects vary across industries and that major benefits are observed in Manufacturing and Energy. The sectors that obtain less benefits are Trade and Transport.
Keywords: H54; R11; R15; C21; 330; Public capital; economic sectors; SURE